Meningkatkan Kinerja Pegawai Kantor Kelurahan Kuta, Badung-Bali: Pendekatan Gaya Kepemimpinan, Motivasi dan Suasana Kerja - Ida Bagus Gede Udiyana; Ni Made Eni Indra Yanti; Ni Nyoman Seri Astini; Ni Ketut Laswitarni; I Nyoman Parta; Ida Bagus Ngurah Wimpascima (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
The purpose of this study was to determine and analyze the leadership style, motivation, and work atmosphere influence on the performance of head-village Office employees, partially and simultaneously. This research was conducted at the Kuta Village Office, Badung Regency with a sample size of 36 people. The data analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t tests and F tests assisted by the SPSS program. The results of this study indicate that partially and simultaneously leadership style, work motivation and work atmosphere have a positive and significant effect on employee performance at the Kuta Village Office, Badung-Bali. So that in an effort to improve employee performance it is recommended that leaders need to involve subordinates in making decisions, give awards to outstanding employees and create a conducive work atmosphere.